A Comparative Analysis of BS Education System with Conventional Education System - Naz, Riffat (The Lighthouse Journal of Social Sciences, 2024)
This study evaluates the effectiveness of Pakistan’s conventional education system in comparison to the BS system, focusing on key factors such as academic quality, standardization, and institutional alignment. Drawing on insights from education experts, subject specialists, and comparative data, the research explores how traditional degree programs may better suit the socio-cultural and institutional framework of Pakistan. Using a mixed-methods approach, data were collected through surveys and interviews with faculty members and students across public universities in KP. The findings indicate that the conventional system, while lacking international recognition, often provides deeper subject knowledge and more rigorous assessment practices. In contrast, the BS system, though aligned with global models, faces implementation challenges in Pakistan due to limited resources, administrative burden, and cost barriers. The study concludes with recommendations for enhancing the conventional model by integrating select features from globally recognized systems, ensuring both academic integrity and practical relevance within the local context.